Organizational Endline Study: Report for Nyando, Kenya - Ogada, Maurice Juma; Chelagat, Risper; Radeny, Maren A.O.; Recha, John W.M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This report summarizes the findings from the Organizational Endline Survey (OES) carried out in Nyando Climate-Smart Village in June and July 2021. The survey is a complementary module to the household and the village endline surveys conducted over the same period. While the household and village surveys provided information from the beneficiaries, OES provided information from the service providers themselves. The three survey modules together provide comprehensive information on the impact of CCAFS interventions over the last ten years.